2016
DOI: 10.1016/j.vaccine.2016.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species prediction of human survival probabilities for accelerated anthrax vaccine absorbed (AVA) regimens and the potential for vaccine and antibiotic dose sparing

Abstract: Anthrax vaccine adsorbed (AVA, BioThrax) was recently approved by the Food and Drug Administration (FDA) for a post-exposure prophylaxis (PEP) indication in adults 18–65 years of age. The schedule is three doses administered subcutaneous (SC) at 2-week intervals (0, 2, and 4 weeks), in conjunction with a 60-day course of antimicrobials. The Public Health Emergency Medical Countermeasures Enterprise (PHEMCE) developed an animal model to support assessment of a shortened antimicrobial PEP duration following Baci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Cessation of antimicrobial treatment at Day 28 would reduce the schedule duration by 32 days. Cross species modeling may be applied to estimate predicted probability of survival in humans receiving schedules matched with the NHP studies [1315]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cessation of antimicrobial treatment at Day 28 would reduce the schedule duration by 32 days. Cross species modeling may be applied to estimate predicted probability of survival in humans receiving schedules matched with the NHP studies [1315]. …”
Section: Discussionmentioning
confidence: 99%
“…In rhesus macaques vaccinated with a three dose priming series of AVA [20] and in this study [15], the anti-PA IgG level at the time of challenge was determined to be the most accurate single measure for determining the probability of survival against an inhalation anthrax challenge, with peak response being the next best alternative. In an extensive analysis of data from multiple studies in several species, Fay, et al [13] found that the TNA measurement could also be used to predict survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the ECL method used to determine the treatment trigger, a PA ELISA directly quantifying the PA in serum was performed retrospectively on frozen serum samples for the quantification of circulating PA on days 1, 2, and 3; immediately pretreatment; and on days 7, 14, 28, and 56, as previously described (32). Toxinneutralizing antibodies and anti-PA IgG titers were monitored by the TNA and the ELISA, respectively, on days 10, 14, 21, 28, 42, and 56 and on each of the 3 days after the last treatment, as previously described (33,34).…”
Section: Methodsmentioning
confidence: 99%
“…The only licensed anthrax vaccine, Anthrax Vaccine Absorbed (AVA, BioThrax ® ), is advisable for active immunization in humans 18-65 years of age at high risk of exposure. The primary immunogen in AVA is PA. AVA induces immunity primarily by stimulating the production of antibodies against PA. Anti-PA antibodies directly neutralize the toxin, inhibiting spore germination, and improve the spore phagocytosis by macrophages [60,61].…”
Section: Bacillus Anthracismentioning
confidence: 99%